Could Toronto Provide 10% of its Fresh Vegetable Requirements from Within its Own Boundaries? Part II, Policy Supports and Program Design - Rod MacRae; Joe Nasr; James Kuhns; Lauren Baker; Russ Christianson; Martin Danyluk; Abra Snider; Eric Gallant; Penny Kaill-Vinish; Marc Michalak; Janet Oswald; Sima Patel; et al. (Journal of Agriculture, Food Systems, and Community Development, 2016)
Urban agriculture in Toronto largely focuses on self-provisioning, but it could be scaled up significantly. Our findings in an earlier paper indicate that the supply of land is not an insurmountable barrier. Rather, other more subtle impediments exist, including taxation systems and structures that assume agriculture is a strictly rural activity; inadequate sharing of knowledge among urban producers; limited access to soil, water, and seeds; and the lack of incentives to attract landowners and foundations to provide financial or in-kind support. The potential exists to develop urban agriculture so that it supplies 10% of the city's commercial demand for fresh vegetables. Scaling up to this level requires significant policy and program initiatives in five key areas: Increasing urban growers' access to spaces for production; putting in place the physical infrastructure and resources for agriculture; integrating local food production into the food supply chain; creating systems for sharing knowledge; and creating new models for governance, coordination, and financing. Our recommendations, while focusing on Toronto, offer lessons for those currently attempting to strengthen urban agriculture in other cities.